The Mechanical Components of the Dynein Motor - Peter Höök (The Scientific World Journal)
Unlike our understanding of the other two classes of cytoskeletal motor proteins, the myosins and kinesins, we have only recently begun to comprehend the molecular mechanism for how dynein produces force and movement. The slow progress has been attributed, in part, to the enormous size of the dynein force-producing head, but also to the complex interplay between its structural components, each of which has a unique role in regulating dynein motor activity. The integrated and highly coordinated mechanism by which these structures work together in powering the dynein machinery is discussed in this review.